Effect of long term CPAP therapy on cardiac parameters assessed with cardiac MRI - Wüst, Wolfgang; May, Matthias; Wiesmüller, Marco; Uder, Michael; Schmid, Andrea (International Journal of Cardiovascular Imaging, 2020)
The obstructive sleep apnoea syndrome (OSAS) is a disorder with a high prevalence and is associated with an elevated cardiovascular risk and increased morbidity and mortality. For longitudinal studies and functional analysis cardiac MRI is regarded as the gold standard. Aim of this study was to evaluate the long-term effect of continuous positive airway pressure (CPAP) therapy on cardiac functional parameters with cardiac Magnetic Resonance Imaging (cMRI). 54 patients with OSAS (mean apnea hypopnea index-AHI: 31) were prospectively enrolled in this study and cMRI was performed before and after 7 months of CPAP therapy. Data were acquired on a 1.5 T MRI and right and left ventricular cardiac function were analysed. CPAP treatment was considered compliant when used ≥ 4 h per night. 24-h blood pressure was measured at baseline and follow up. 33 patients could be assigned to the compliance group. Left ventricular stroke volume (LV SV) and right ventricular ejection fraction (RV EF) improved significantly with CPAP therapy (LV SV from 93 ± 19 to 99 ± 20 ml, p = 0.02; RV EF from 50 ± 6 to 52 ± 6%, p = 0.04). All other cardiac parameters did not change significantly while mean systolic and diastolic blood pressure improved significantly (p < 0.01). 21 patients were assigned to the non-compliance group and were considered as a control group. There were no relevant differences in cardiac parameters between baseline and follow up examination in these patients. CPAP therapy seems to improve LV SV, RV EF, systolic and diastolic blood pressure in OSAS patients, but reproducibility of our results need to be confirmed in a larger patient population.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Cardiac MRI; CPAP therapy; Follow up; Sleep apnea